A digital storytelling process guide for designers - Hussain, Hashiroh; Shiratuddin, Norshuhada (Universiti Teknikal Malaysia Melaka, 2016)
Digital Storytelling (DST) is a method of delivering information to the audience using narrative and digital media contents that are infused with the multimedia elements.In order for the educators cum the designers to create a compelling digital story, experts have proposed a number of phases.Nevertheless, some of these suggested phases contain redundant processes. Therefore, the main aim of this study is to eliminate the redundancy and propose a single DST guide for the designers.A comparative analysis was employed where ten DST models from various experts were analysed.The proposed guide was then distributed to 70 respondents in an Institute of Teacher Education (ITE). Data were analysed to determine the relationships between factors such as perceived usefulness, perceived of use, perceived ease of understanding and interaction of tablet with the overall quality of the DST process. The correlation analysis indicates that higher scores of the factors are associated with higher score of the overall quality of the DST process